Antioxidant Activity of Hydnophytum formicarum Extract by TEAC method (Trolox Equivalent Antioxidant Capacity Assay) - Purnamasari, Mayshah (Hydrogen: Jurnal Kependidikan Kimia, 2024)
Oxidative stress, caused by excess reactive oxygen species (ROS), is believed to be a major contributor to aging and various degenerative diseases. Plant-based antioxidants have gained significant attention for their potential in combating R.O.S. Hydnophytum formicarum, traditionally used to treat diabetes, is evaluated as a natural antioxidant source. This study is the first to assess the antioxidant activity of H. formicarum tuber ethanol extract using the TEAC method, revealing a high antioxidant capacity (220.38 Â± 0.61 M TE/100 g), highlighting its potential as a dietary supplement.